Effect of a physical training program on the occurrence of exercise-induced arrhythmias in patients with heart disease - Espinoza Perez, Jessica (2021)
Objective. Although physical training has been associated with an increase in survival, its role in reducing Exercise-induced arrhythmias (EIA) in patients with heart disease has not yet been dilucidated. We aim to compare the effect of physical training on the occurrence of EIA in patients with heart disease. Methodology. We evaluated a retroprospective and self-controlled cohort of patients older than 18 years with heart disease who entered the cardiac rehabilitation program of the National Institute of Cardiology Ignacio Chávez in México, during January 2005 to December 2016. In all patients, cardiovascular risk was stratified, including a cardiopulmonary exercise test, which was also performed at the end of the program. The occurrence of arrhythmias was evaluated before and after the training program. Results. 160 patients were analyzed, of which 126 (79%) were male. The proportion of patients who developed EIA in the first exercise testing was 56% and in the second one was 48%. In the first group 35% of patients did not developed EIA in the second test. Of the 71 patients who did not present EIA at the beginning of the program, twenty (28%) presented arrhythmias at second test. In relation to the effect of the training program on the occurrence of arrhythmias, we could observe that it had a protective effect, with a RR = 0.49 (95% CI: 0.35-0.67, p <0.001). Conclusion. In this study, physical training was associated with a decreased risk of developing EIA.